Low temperature difference thermoacoustic prime mover with asymmetric multi-stage loop configuration - T. Jin (Scientific Reports, 2017)
Abstract Environmentally friendly and low-cost technologies to recover low-grade heat source into usable energy can contribute to ease the energy shortage. Thermoacoustic technology is expected as one promising approach in this ascendant field. In this work, the multi-stage looped thermoacoustic prime movers with asymmetric configuration, which can provide travelling-wave resonator and appropriate acoustic field for efficient regenerator, have been proposed and experimentally studied. The presented looped thermoacoustic prime movers can start to oscillate with quite low temperature difference along the regenerator. The lowest onset temperature difference obtained in the experiments is only 17 °C (the corresponding heating temperature is 29 °C), which can be achieved in both three-stage and four-stage looped thermoacoustic prime movers, with CO2 of 1 MPa or 1.5 MPa as the working fluid. An electric generator driven by a three-stage looped thermoacoustic prime mover with low heating temperature was tested to achieve the acoustic to electric conversion.